CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2468747
|View full text |Cite
|
Sign up to set email alerts
|

Smart pose

Abstract: With the widespread use of smartphones, users tend to use their smartphones for a long period of time with unhealthy postures, bending forward their upper body including the neck. If users keep such an unhealthy posture for a long time, their neck and back muscles get chronically strained, which might cause diseases such as cervical myalgia. To prevent these diseases, we propose a new methodology to monitor the posture of smartphone users with built-in sensors. The proposed mechanism estimates a value represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Yoo et al proposed capturing the user's facial expressions through the front-facing camera for lifelogging applications [50]. EyeProtector and SmartPose leveraged users' face size in the front-facing camera view to warn users if they were too close to the screen [22,35]. There is also a large body of work about authentication via face recognition on mobile devices [40], such as FaceID.…”
Section: Face and Eyes Detection On Commodity Smartphonesmentioning
confidence: 99%
“…Yoo et al proposed capturing the user's facial expressions through the front-facing camera for lifelogging applications [50]. EyeProtector and SmartPose leveraged users' face size in the front-facing camera view to warn users if they were too close to the screen [22,35]. There is also a large body of work about authentication via face recognition on mobile devices [40], such as FaceID.…”
Section: Face and Eyes Detection On Commodity Smartphonesmentioning
confidence: 99%
“…The study was comprehensive but lacked a proper notification or warning mechanism [8]. Another study by Hosub Lee et al used an orientation sensor and the front camera of a smartphone to monitor the posture of the human body [9]. The drawback lied in the usage of two internal sensors of the smartphone-the triaxial Accelerometer and Magnetic Sensor (compass) to get [11].…”
Section: Related Workmentioning
confidence: 99%
“…Many of the applications, for example, Smart Pose, proposed in a past research paper, warns the user only momentarily; however, datum is not collected or reported over the day, week, or months [9]. Spined stores all the data of the posture in a local SQLite Database that is created when the app is first installed.…”
Section: Databasementioning
confidence: 99%
“…Nonetheless, these proposals did not provide accurate measurements of the neck movement or angle. Smart Pose is one of the latest studies attempting to find a preventive solution for this syndrome. The authors of Smart Pose developed a system based on the sensors embedded in modern smartphones.…”
Section: Related Studiesmentioning
confidence: 99%